Vegetation Analysis and Carbon Stock Estimation of Mangrove Island on Mangrove Ecotourism in Gebang Village, Lampung - Eti Artiningsih Octaviani; Nurika Arum Sari (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2022)
Mangrove forests have an important role in reducing the effects of global warming. This study aims to analyze vegetation and estimate carbon stock in mangrove stands in the Mangrove Island of Petengoran Mangrove Ecotourism Area, Gebang Village, Lampung. The forest vegetation analysis method used is the plotted path method. Paths and plots were taken systematically with tree observation plots made measuring 20 m x 20 m. Carbon estimation was carried out by non-destructive sampling method using the allometric formula for Rhizophora apiculata log BBA= -1.315 + 2.614 log D. The results showed that the mangrove island zone was dominated by Rhizophora apiculata vegetation with a density of 325 ind/Ha. The research location has a silty clay loam soil texture with a temperature range of 25°C-32°C which is very suitable for the vegetation of R. apiculata. The estimated carbon stored in the vegetation was obtained from 46% of the standing biomass of R. apiculata, which was 86,283 tons C/Ha.